'Diversity' policies, integration and internal security: The case of France. (December 2014) - Mattelart, Tristan; Hargreaves, Alec G
The term 'cultural diversity' has been widely used in France since the beginning of the 21st century as a standard way of referring to policies aimed at improving the representation of ethnic minorities in the audio-visual media. Frequently invoked, the notion of 'diversity' is seldom questioned. While endowed with a powerful incantatory power, it is not without its problems. Its looseness obfuscates the policy objectives pursued in its name, just as its seeming novelty prevents us from seeing those initiatives in a historical perspective. Tracing the genealogy of diversity policies in France, this article demonstrates that they have sought not only to promote the integration of ethnic minorities but also – and no less importantly – to protect internal security.